Saints on Stage: Popular Hagiography in Post-WWII Italy - Daniela Cavallaro (Religions, 2021)
This article brings to light several examples of the hagiographic plays staged in Italy during the 1950s and early 1960s in parishes, schools, and oratories. The article begins with a brief introduction to the continued tradition of staging the lives of the saints for educational purposes, which focuses on the origins, aims, and main characteristics of theatre for young people of the Salesians, the order founded by Don Bosco in 1859. Next, it offers a brief panorama of the pervasive presence of the lives of the saints in post-WWII Italy. The main discussion of the article concerns the hagiographic plays created for the Salesian educational stages in the years between 1950 and 1965, especially those regarding the lives of young saints Agnes and Domenico Savio. The article concludes that the Salesian plays on the lives of the saints, far from constituting a mere exercise in hagiography, had a definite educational goal which applied to both performers and audiences in the specific times of Italy’s reconstruction and the cold war.